2013
DOI: 10.1371/journal.pone.0058936
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Weight Loss Mediates Sexual Size Dimorphism in Drosophila melanogaster

Abstract: The selective pressures leading to the evolution of Sexual Size Dimorphism (SSD) have been well studied in many organisms, yet, the underlying developmental mechanisms are poorly understood. By generating a complete growth profile by sex in Drosophila melanogaster, we describe the sex-specific pattern of growth responsible for SSD. Growth rate and critical size for pupariation significantly contributed to adult SSD, whereas duration of growth did not. Surprisingly, SSD at peak larval mass was twice that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
111
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 82 publications
(127 citation statements)
references
References 41 publications
(39 reference statements)
12
111
0
Order By: Relevance
“…The hypoallometric pattern for SSD and isometric pattern for SDtD are thus qualitatively inconsistent, and therefore the sex differences, as well as the SSD allometry not following Rensch's rule displayed in Figure 2, are only distinct for wing size (and not developmental time), which is also true across Drosophila species (Blanckenhorn et al, 2007a). Overall, therefore, sex differences in developmental time cannot explain sex differences in body size, and SDtD cannot explain the allometric pattern of SSD in any simple way, confirming similar conclusions of previous studies (Blanckenhorn et al, 2007a;Testa et al, 2013). Contrary to expectation, we here also found a significant negative genetic correlation between wing size and developmental time that was equal for both sexes (Figure 3).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The hypoallometric pattern for SSD and isometric pattern for SDtD are thus qualitatively inconsistent, and therefore the sex differences, as well as the SSD allometry not following Rensch's rule displayed in Figure 2, are only distinct for wing size (and not developmental time), which is also true across Drosophila species (Blanckenhorn et al, 2007a). Overall, therefore, sex differences in developmental time cannot explain sex differences in body size, and SDtD cannot explain the allometric pattern of SSD in any simple way, confirming similar conclusions of previous studies (Blanckenhorn et al, 2007a;Testa et al, 2013). Contrary to expectation, we here also found a significant negative genetic correlation between wing size and developmental time that was equal for both sexes (Figure 3).…”
Section: Discussionsupporting
confidence: 85%
“…Testa et al (2013) described complete growth profiles of D. melanogaster males and females, and identified sex-specific growth factors responsible for SSD. They found that growth rate and critical size for pupation significantly contributed to SSD, while developmental time did not.…”
Section: Introductionmentioning
confidence: 99%
“…For the measurement of larval growth trajectories at 258C, female larvae also carried a ubi-GFP transgene (Bloomington Stock Center, 1681) that had been backcrossed into SAM for five generations. This allowed us to conduct experiments exploring the developmental regulation of sexual size dimorphism, described elsewhere [36]. All experiments were conducted at constantlight regime, and fly cultures were maintained at low density (50-60 larvae per 6 ml food) on standard cornmeal -molasses medium.…”
Section: Methods (A) Fly Stocks and Rearingmentioning
confidence: 99%
“…1A shows that ablation of the CA had no effect on critical weight. We used the breakpoint method to assay critical weight in CAX and control larvae (15,(20)(21)(22). This method exploits the fact that the relationship between larval weight at starvation and time to pupariation (TTP) changes at critical weight (Fig.…”
Section: Significancementioning
confidence: 99%